Bright Bacterium for Hypoxia‐Tolerant Photodynamic Therapy Against Orthotopic Colon Tumors by an Interventional Method. Issue 15 (18th June 2021) - Zhu, Daoming; Zhang, Jing; Luo, Guanghong; Duo, Yanhong; Tang, Ben Zhong
Abstract: While promising, the efficacy of aggregation‐induced emission (AIE)‐based photodynamic therapy (PDT) is limited by several factors including limited depth of laser penetration and intratumoral hypoxia. In the present study, a novel bacteria‐based AIEgen (TBP‐2) hybrid system (AE) is developed, that is able to facilitate the hypoxia‐tolerant PDT treatment of orthotopic colon tumors via an interventional method. For this approach, an interventional device is initially designed, composed of an optical fiber and an endoscope, allowing for clear visualization of the position of the orthotopic tumor within the abdominal cavity. It is then possible to conduct successful PDT treatment of this hypoxic tumor via laser irradiation, as the TBP‐2 is able to generate hydroxyl radicals (OH) via a type I mechanism within this hypoxic microenvironment. Moreover, this interventional approach is proved to significantly impair orthotopic colon cancer growth and overcame PDT defects. This study is the first report involving such an interventional PDT strategy to knowledge, and it has the potential to complement other treatment modalities while also highlighting novel approaches to the design of hybrid AIEgen systems. Abstract : A novel bacteria‐based AIEgen hybrid system that is able to facilitate the hypoxia‐tolerant PDT treatment of orthotopic colon tumors via an interventional method is developed. This interventional approach is proved to significantly impair orthotopic colon cancer growth and overcame PDT defects.